Atypical spinal cord infarction: A case report. Issue 23 (June 2018) - Ota, Koshi; Iida, Ryo; Ota, Kanna; Sakaue, Masahide; Takashima, Shogo; Taniguchi, Kohei; Tomioka, Masao; Nitta, Masahiko; Takasu, Akira
Abstract: Introduction: The abrupt onset of sensorimotor deficits is a neurologic emergency that requires immediate management. Acute spontaneous spinal cord infarction (SCI) is rare, but can cause the sudden onset of quadriplegia or quadriparesis. Magnetic resonance imaging (MRI) is an essential imaging modality to diagnose SCI. Case presentation: A 75-year-old man with a history of diabetes mellitus type 2, hypertension, and dyslipidemia was transferred to our facility for further workup of the sudden onset of quadriplegia. Diffusion-weighted contrast MRI (DWI) on hospital day 8 revealed hyperintense signals predominantly at the grey matter, and a contrast T2 signal abnormality with a decreased apparent diffusion coefficient (ADC). Steroid pulse therapy was initiated because myelitis could not be completely ruled out, but this did not improve the neurological deficits. Spontaneous SCI was finally diagnosed as an exclusion diagnosis. Symptoms were gradually recovered with rehabilitation, and he was transferred to a rehabilitation facility on hospital day 40. Conclusion: MRI with DWI of the spine should be considered for an early diagnosis of SCI. A combination of DWI with ADC maps is recommended to distinguish SCI from other differential disorders.